Application of online teaching mode combining case studies and the MOOC platform in obstetrics and gynecology probation teaching - Yi Li; Chunfen Yang; Wenyan Liao; Shuangjian Yang; Wenjuan Tong; Li Li; Hui Lan; Dong Yang (BMC Medical Education, 2022)
Abstract Objective To explore the application effect of the clinical basic integration teaching mode constructed by case studies and the MOOC platform in obstetrics and gynecology internship teaching in the face of public health emergencies. Methods One hundred ten clinical medical students of grade 2020 were selected as the experimental group, and 110 clinical medical students of grade 2021 were selected as the control group. The experimental group adopted the online teaching mode combined with case studies and the MOOC platform, while the control group adopted the offline traditional probation teaching method. Comprehensive test and questionnaire were used to evaluate and compare the teaching effect of the two groups of students. Results The experimental group was found to be superior to the control group in the quality assessment of complete medical record writing and the ability assessment of diagnosis and analysis of typical obstetrics and gynecology cases (P < 0. 05). However, the score of professional knowledge was lower than that of the control group (P < 0. 05). The results of questionnaire survey showed that the satisfaction of the experimental group in stimulating learning interest, enhancing problem solving ability, enhancing communication and clinical thinking ability, enhancing team cooperation awareness and independent innovation ability was higher than that of the control group (P < 0.01). The satisfaction of teacher-student interaction was also better (P < 0.05). However, in terms of strengthening theoretical understanding, the satisfaction of the experimental group was lower than that of the control group, but with no significant difference (P > 0.05). Conclusion During the epidemic period, we designed a new online teaching mode, which can be applied to the probation teaching of obstetrics and gynecology. In our study, compared with traditional offline teaching, the new online teaching mode could improve students’ ability of case writing and case analysis. However, more teaching practice is needed to complete this online teaching mode.